Climate impacts, forest-dependent rural livelihoods and adaptation strategies in Africa: A review - Somorin, O.A. (2010)
The long term contribution of forests to the livelihoods of the rural poor had been long appreciated. More than half of Africa’s fast-growing population rely directly and indirectly on forests for their livelihoods. As the continent faces stresses from poverty and economic development, another major uncertainty is looming that could alter many of the relationships between people and forests. This uncertainty is climate change. Climate impacts such as changes in temperature and rainfall patterns resulting in drought, flooding, all exert significant effect on forest ecosystems and their provision of goods and services, which form the safety nets for many African rural poor. Building adaptation strategies becomes an option for forest-dependent households and communities, and even countries whose economies largely depend on the related sectors. The review details cases of impacts, underlying causes of vulnerability, and identified coping and adaptation strategies, as reported in their National Communications by many African countries to the United Nations Framework Convention for Climate Change.